Improvement Productivity Chicken Village through Implementation Modern Cages and Feed Fermentation Based Material Local - Irmayani Irmayani; Rasbawati Rasbawati; Sri Nurqadri (MALLOMO: Journal of Community Service, 2026)
This community service activity was initiated in response to the low productivity of native chickens caused by traditional management practices and limited farmer knowledge this is feed and housing management. The program aims to enhance productivity through the application of improved housing system and fermented feed based on locally available ingredients. The approach involved the provision of simple but more hygienic chicken housing, distribution of chickens and feed, and training accompanied by continuous assistance for farmers on proper management practices and the preparation of fermented feed using rice bran, ground corn, concentrate, and moringa leaf meal [processed with probiotic solutions. The results indicated a significant improvement in farmers' knowledge and skills, reflected in better feeling management, improved sanitation of housing , and reduced mortality rates. Furthermore, the use of fermented feed contributed to better feed efficiency and supported improved growth performance of the chickens. Farmers also gained an understanding of basic marketing strategies to increase the economic value of their products. In conclusion, the implementation of improved housing and fermented feed based on local resources provides a positive impact on increasing native chicken productivity and supports the development of sustainable and independent agricultural -scale farming practices